Adsorption and Inhibitive Properties of Lincomycin for the Corrosion of Zinc in 0.01 - 0.05 M H2SO4 - Eddy,N.O. (2010)
Inhibition of the corrosion of zinc in various concentrations of H2SO4 by lincomycin was studied using weight loss and hydrogen evolution methods. The results obtained indicated that lincomycin is a good adsorption inhibitor for the corrosion of zinc in H2SO4 solutions. The inhibition efficiencies of lincomycin for the corrosion of zinc in H2SO4 were found to range from 70.90 to 80.32 %, 69.25 to 77.70 % and from 52.11 to 67.49 % at 303, 313 and 323 K, respectively. The inhibition efficiencies decreased with increase in temperature and with increasing concentration of H2SO4 but increased with increase in the concentration of lincomycin. The adsorption of lincomycin on Zn surface is endothermic, spontaneous and is best described by Langmuir adsorption isotherm. Base on the trend in the variation of inhibition efficiency with temperature and the calculated values of the activation and free energies of adsorption, a physical adsorption mechanism is proposed for the adsorption of lincomycin on the surface of zinc.